Solidification of nanosuspensions for the production of solid oral dosage forms and inhalable dry powders. (3rd March 2016) - Malamatari, Maria; Somavarapu, Satyanarayana; Taylor, Kevin M.G.; Buckton, Graham
Abstract: Introduction : Nanosuspensions combine the advantages of nanotherapeutics (e.g. increased dissolution rate and saturation solubility) with ease of commercialisation. Transformation of nanosuspensions to solid oral and inhalable dosage forms minimises the physical instability associated with their liquid state, enhances patient compliance and enables targeted oral and pulmonary drug delivery. Areas covered : This review outlines solidification methods for nanosuspensions. It includes spray and freeze drying as the most widely used techniques. Fluidised-bed coating, granulation and pelletisation are also discussed as they yield nanocrystalline formulations with more straightforward downstream processing to tablets or capsules. Spray-freeze drying, aerosol flow reactor and printing of nanosuspensions are also presented as promising alternative solidification techniques. Results regarding the solid state, in vitro dissolution and/or aerosolisation efficiency of the nanocrystalline formulations are given and combined with available in vivo data. Focus is placed on the redispersibility of the solid nanocrystalline formulations, which is a prerequisite for their clinical application. Expert opinion : A few solidified nanocrystalline products are already on the market and many more are in development. Oral and inhalable nanoparticle formulations are expected to have great potential especially in the areas of personalised medicine and delivery of high drug doses (e.g. antibiotics) to the lungs, respectively.